Otroci in mladostniki v prostoru - Simoneti, Maja (Urbani izziv, 2000)
The last decade of Slovenian planning practice has left visible consequences in spatial uses, that depend on long-term definitions and principles. Mainly those types of land use were affected, that are tighthly connected with the public good and public interest. Amongst other they include the spatial needs of children and adolescents. The article presents findings on spatial conditions for the life of children and youth. The analysis of conditions in Ljubljana reveals a wide range of problems, in the system and presently prevailing operative level. Owing to a lack of urbanistic and security norms we are on a course of gradual decay of the inherited network of childrens playgrounds and disrespect for the spatial needs of children and younger population. The aim of the article is to disclose the present peripheral importance of the issue in spatial reality and expert debate, that is in contradiction with the declared importance of this population group.
Keywords: child; Ljubljana; mesta; mladina; otroci; otroška igrišča; prostorsko planiranje; prostorsko urejanje; spatial planning; zelene površine